The impact of cryptocurrencies market development on banks’ deposits variability in the GCC region - Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Ashurov, Sharofiddin (Emerald Publisher, 2019)
Purpose With the continuing development of the financial technology revolution, a better understanding of bank deposits variability has become necessary for bank management and policymakers, especially central banks. This is because the novel innovations of cryptocurrencies operate beyond the realm of the banking system, which may impact the performance of banks and their deposits variability. This study aims to investigate the long- and short-run effects of cryptocurrencies’ market capitalization development on the banks’ deposit variability in the Gulf Cooperation Council (GCC) region. Design/methodology/approach In this study, the Johansen–Juselius (1990) cointegration test with vector error correction model was applied to examine the long-run relationships, while the Engle and Granger (1987) and the Granger (1969) causality tests were used to detect causal relationships in the short term. Findings The findings of Johansen–Juselius cointegration test indicate that the banks’ deposits variability in all six states of the Gulf region share negative long-run equilibrium association with the development of global cryptocurrencies market capitalization, but with different statistically significant levels. For the short-run analysis, the study found that the development of cryptocurrencies market capitalization has significant unidirectional causal effects on bank deposits variabilities in only four states, namely, UAE, Qatar, Kuwait and Bahrain. The findings of the study therefore suggest that to eradicate the effects of cryptocurrencies industry and its threats to the banking industry, banks in GCC region are encouraged to either consider cryptocurrencies as an alternative investment asset for their portfolio investment diversification strategies or adopt the blockchain technology in their operation system to facilitate their customers with low transaction cost, high level of security and ease of use and real-time settlement. Research limitations/implications The empirical findings of the study will provide valuable input for policymakers, especially central banks and bank managements, to evaluate the current situation and the threats of the cryptocurrencies market growth and its effect on the banking industry’s performance, future survival and their deposits variability for better regulation and policy planning and investment strategies. Originality/value This is a pioneering study that empirically explores the phenomenon of bank deposits variability as a consequence of expansion in cryptocurrencies market capitalization, where the findings proved evidence of a drastic decline in banks’ deposits size due to the substantial growth in cryptocurrencies market capitalization.